The Effect of Service Quality and Customer Satisfaction on Customer Loyalty in the Banking Sector - Delia Siti Nurhalizah; Muji Rahayu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effect of service quality and customer satisfaction on customer loyalty at Bank Tabungan Negara (BTN) Rancaekek. The study is motivated by the increasingly intense competition in the banking industry and the rising expectations of customers for fast reliable and professional services particularly in peri urban areas experiencing rapid economic growth. The research gap lies in the persistence of inconsistent empirical findings regarding the role of service quality and customer satisfaction in shaping customer loyalty especially within the context of regional banking institutions. This study employs a descriptive quantitative approach using a survey method. The research subjects consist of active customers of BTN Rancaekek who have used the bank’s services for at least six months. The population was selected using purposive sampling while the sample was determined through probability random sampling with a total of 122 respondents. Data were collected through a questionnaire distributed using a five point Likert scale and analyzed using SPSS through validity and reliability tests linear regression analysis and both partial and simultaneous hypothesis testing. The results indicate that partially service quality has a positive and significant effect on customer loyalty. Similarly customer satisfaction is proven to have a positive and significant effect on customer loyalty although with a relatively smaller contribution. Simultaneously service quality and customer satisfaction are shown to have a significant influence on customer loyalty. These findings confirm that improving service quality accompanied by the creation of customer satisfaction is a key factor in building and sustaining customer loyalty.